Contextualising risk: the unfolding information work and practices of people during the COVID-19 pandemic. Issue 5 (22nd February 2021) - Lloyd, Annemaree; Hicks, Alison
Abstract : Purpose: The aim of this study is to investigate people's information practices as the SARS-CoV-2 virus took hold in the UK. Of particular interest is how people transition into newly created pandemic information environments and the ways information literacy practices come into view. Design/methodology/approach: The qualitative research design comprised one-to-one in-depth interviews conducted virtually towards the end of the UK's first lockdown phase in May–July 2020. Data were coded and analysed by the researchers using constant comparative and situated analysis techniques. Findings: Transition into new pandemic information environments was shaped by an unfolding phase, an intensification phase and a stable phase. Information literacy emerged as a form of safeguarding as participants engaged in information activities designed to mitigate health, legal, financial and well-being risks produced by the pandemic. Research limitations/implications: Time constraints meant that the sample from the first phase of this study skewed female. Practical implications: Findings establish foundational knowledge for public health and information professionals tasked with shaping public communication during times of crisis. Social implications: This paper contributes to understandings of the role that information and information literacy play within global and long-term crises. Originality/value: This is one of the first studies to explore information practices during the COVID-19 pandemic.